2007
DOI: 10.1021/jo071010m
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Transformation of Octaethylporphyrin into a Phytoporphyrin Analogue

Abstract: An octaethylporphyrin derivative, 1, possessing an exo-five-membered ring fused at the 13- and 15-positions was oxidized by osmium tetroxide to give two isomeric chlorins, 3 and 5, possessing beta,beta'-dihydroxy groups at the A- and C-rings, respectively. Single dehydration of 2,3-dihydroxychlorin 3 gave a mixture of 2- and 3-(1-hydroxyethyl)porphyrins 7, while that of 12,13-dihydroxychlorin 5 resulted in the sole formation of 131-hydroxyporphyrin 9. The latter was modified smoothly to the phytoporphyrin anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Thus, the phytoporphyrin analogue 5-H 2 17 was treated to the standard conditions for vicinal dihydroxylation with OsO 4 (Scheme ). Chlorins 5-H 2 18a and 5-H 2 18c were obtained (each as a racemic mixture) in yields of 25% and 31%, respectively, along with recovery of the starting porphyrin in 24% yield. While trace pigments with chlorin absorption features also were noted, none was isolated; hence, at best only trace quantities of 5-H 2 18b and 5-H 2 18d were obtained.…”
Section: Oso4-mediated Chlorin Formation From Porphyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the phytoporphyrin analogue 5-H 2 17 was treated to the standard conditions for vicinal dihydroxylation with OsO 4 (Scheme ). Chlorins 5-H 2 18a and 5-H 2 18c were obtained (each as a racemic mixture) in yields of 25% and 31%, respectively, along with recovery of the starting porphyrin in 24% yield. While trace pigments with chlorin absorption features also were noted, none was isolated; hence, at best only trace quantities of 5-H 2 18b and 5-H 2 18d were obtained.…”
Section: Oso4-mediated Chlorin Formation From Porphyrinsmentioning
confidence: 99%
“…The tautomers are of course equivalent for the symmetric octaethylporphyrin, but the presence of the phorbine framework (i.e., the isocyclic ring here lacking the 13 1 -oxo group) renders such tautomers inequivalent. Indeed, calculations indicated that tautomer 5-H 2 17 is more stable than 5-H 2 17-taut (Scheme ); the former contains “cryptoolefins” in rings A and C whereas the latter contains the isolated double bonds in rings B and D. The greater stability of 5-H 2 17 versus tautomer 5-H 2 17-taut thereby accounts for the selective formation of chlorins 5-H 2 18a,c versus 5-H 2 18b,d …”
Section: Oso4-mediated Chlorin Formation From Porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2,3dihydroxy moiety of 5 was a useful starting point for modifying the β-positions on the A-ring as mentioned above 19 and was doubly dehydrated by refluxing a benzene solution containing concd HCl, affording 2-and 3-vinylporphyrins 7 (69% yield). The regioisomeric ratio (2:1) was the same as in the previously reported monodehydration of 5 giving 2-and 3-(1-hydroxyethyl)porphyrins, 19 which was reasonable because the present bis-dehydration proceeded via the monodehydrated intermediate. At this stage, it had not been determined which regioisomer was major, and the mixture of 2-and 3-vinylpoprhyrins was used for the next step.…”
Section: Resultsmentioning
confidence: 99%
“…The regioisomeric ratio of the product 9 was 2:1 which was the same as that of the starting material 8, so the 2-and 3-formyl groups in 8 did not affect the yield of the 12,13-dihydroxylation. The dihydroxy moiety of 9 was also transformed to the 13 1 -oxo group by the same procedures as reported (6 f 14 f 15), 19 affording 2-and 3-formylated phytoporphyrin analogues 11. The initial step, monodehydration of the cis-diol 9 (v in Scheme 1), regioselectively gave 13 1 -OH-10 (64%), so change of the functional group at the A-ring (ethyl to formyl, 6 to 9) still followed the reaction rule via a sole allyl-type carbocation at the 13 1 -position as its intermediate.…”
Section: Jocfeatured Articlementioning
confidence: 99%